Kompetensi Profesional Guru, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja Guru - Lilik Rachmawati; Laurens Kaluge (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2020)
Abstract The success of the national education system can be seen from the performance of teachers. Teacher performance is expected to boost the quality and relevance of education, in its implementation depends on many factors that influence it and interrelated, such factors competence, motivation and discipline. This research is aimed to analyze the effect simultaneously (together) or partially (individually) between teacher professional competence, work motivation, and work discipline on teacher performance. The method used in this research is quantitative with the type of explanatory research and a sample of 120 teachers taken using proportional random sampling techniques. The results showed the teacher's professional competence, work motivation, and work discipline simultaneously had effect on teacher performance. Teacher professional competence has effect on teacher performance. Work motivation has effect on teacher performance. Work discipline has effect on teacher performance.